"Carrying the culture … ": Ethnic identity development in black African adolescents. Issue 2 (24th April 2017) - du Plessis, Jolandie; Naudé, Luzelle
Abstract : This study explored the ethnic identity exploration, commitment, and strength statuses in black African adolescents from the central region of South Africa. A total of 388 adolescents were recruited for this study (females = 66.24%; age range 13 to 21; Setswana = 22.42%; Sesotho = 61.08%, isiXhosa = 16.49%). The adolescents completed a survey battery measuring ethnic identity exploration, commitment, and strength. They also participated in focus group discussions regarding the challenges of developing a black African identity in a changing South African environment. Findings indicate the adolescents to be intensely engaged in ethnic identity exploration, commitment, and strength as evidenced by high scores on the survey battery. The female adolescents self-reported with higher rates of exploration, commitment, and strength compared to their male peers. Setswana adolescents self-reported with consistently lower scores than the other ethnic groups sampled for this study. Adolescents appear to experience the complexities of searching for and committing to an ethnic identity within the multi-cultural and transitioning society of South Africa.